Essays in world economics - Hicks, John (Oxford, Clarendon Press, 1959)
The essays maintain that the liberal goods in economics are goods; that they are values which must be weighed up against other values. The freedom and the justice that are possible of attainment are not the same in all societies, at all times, and in all place; they are themselves conditioned by external environment, and by what has occurred in the past.
Includes index
oif 08/02/2019
Loans
Keywords: Economic policy; Economics; Great Britain